Results of a National Survey of Early Literacy Programs - Balla-Boudrea, Naomi; O'Reilly, Deirdre; Howard, Vivian; McDougall, Carol (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This conference paper reports on a national survey conducted in the summer of 2010 which sought to identify programs and gather information on their operations, programming and challenges. This research project was a joint initiative of the Nova Scotia Read to Me! early literacy program and Dalhousie University’s School of Information Management. Cette communication porte sur un sondage national effectué au cours de l’été 2010 et dont l’objectif était d’identifier les programmes d’alphabétisation et d’obtenir de l’information quant à leur opération, aux activités et aux défis. Ce projet de recherche est une initiative conjointe du programme d’alphabétisation chez les jeunes enfants Nova Scotia Read to Me! et de la School of Information Management de l’Université Dalhousie.